Endoscopic Features of Changes in Gastric Mucosa at Chronic CagA-positive Hр-associated Gastritis in Children - O.Ye. Abaturov; N.Yu. Zavhorodnia (Zaslavsky O.Yu., 2015)
The article presents the results of the comparative analysis of standard endoscopy of the gastric mucosa in children with chronic Helicobacter pylori-associated gastritis taking into account cytotoxicity of Helicobacter pylori strain. Specific endoscopic features of pathological changes in the gastric mucosa of children with chronic gastritis, associated with cytotoxiс strains of Helicobacter pylori, have been determined.